The relationship between anthropometric characteristics and motoric performance of female futsal players - Ari, Y. (International Journal of Applied Exercise Physiology, 2020)
The aim of this study is analyzing the relationship between anthropometric characteristics and motoric performance of female futsal players. 17 female futsal players participated in the study. Vertical jumping, 10 meter acceleration, 20 meter speed and zigzag running agility tests, and anthropometric measurements were used for the performance evaluation. 'Shapiro-Wilk' test was used for normal distribution analysis. 'Pearson's Product-Moment Analysis' was used in the correlation analysis of normal distributed data while 'Spearman's Rank Correlation Coefficient' was used in the correlation analysis of nonnormal distributed data. Significant relationships were detected among the acceleration test values and the speed and zigzag running agility test values (respectively; r = .634, p<0.01; r = .592, p<0.05). A significant relationship was detected between speed and zigzag running agility test values (r = .525, p<0.05). Significant negative relationships were detected among the vertical jumping test values and speed and zigzag running agility test values (respectively; rho = -.545, p<0.05; rho = -.551, p<0.05). No relation was detected between anthropometric characteristics and motoric performances (p>0.05). As a result, to improve motoric performance with anthropometric characteristics it is suggested that a distinct education strategy within the current training program should be prepared.